Description of the Role of Islamic Religious Education Teachers in Developing Students' Akhlakul Karimah - Hamdana; Zaim, Nabillah Huda (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The purpose of this study was to find out the description of the teacher's role in shaping the akhlakul karimah students at the Junior High School Methodology: The method in this research is a quantitative method. Data analysis is the process of organizing and sorting data into patterns, categories, and basic descriptive units so that hypotheses can be found and formulated as suggested by the data. Main Findings: The results showed that the teacher's role is very important to form students' akhlakul karimah. The importance of having akhlakul karimah for students is to be able to always coexist and be harmonious. By having good morals, of course someone will not dare to do damage. Good morals will be a fortress, will be a shield or protector in every step of life. Novelty/Originality of this study: The teacher's efforts in instilling akhlakul karimah to students through several methods, namely, exemplary, advice, motivation, punishment, habituation, gift giving, and supervision. The teacher supervises student behavior both in the school environment and outside the school environment. So that the role of the teacher is very important in shaping student morality.